Transcriptional regulation of myeloid-derived suppressor cells. Issue 6 (3rd September 2015) - Condamine, Thomas; Mastio, Jérôme; Gabrilovich, Dmitry I
Abstract : Review of transcription factors that regulate MDSC expansion and accumulation. Abstract: Myeloid-derived suppressor cells are a heterogeneous group of pathologically activated immature cells that play a major role in the negative regulation of the immune response in cancer, autoimmunity, many chronic infections, and inflammatory conditions, as well as in the regulation of tumor angiogenesis, tumor cell invasion, and metastases. Accumulation of myeloid-derived suppressor cells is governed by a network of transcriptional regulators that could be combined into 2 partially overlapping groups: factors promoting myelopoiesis and preventing differentiation of mature myeloid cells and factors promoting pathologic activation of myeloid-derived suppressor cells. In this review, we discuss the specific nature of these factors and their impact on myeloid-derived suppressor cell development.